2004
DOI: 10.1097/01.gme.0000142887.31811.97
|View full text |Cite
|
Sign up to set email alerts
|

The effects of postmenopausal hormone therapies on female sexual functioning: a review of double-blind, randomized controlled trials

Abstract: Double-blind randomized controlled trials of estrogen and/or testosterone on sexual function among natural or surgical menopause in women are reviewed. Power, validity, hormone levels, and methodological issues were examined. Certain types of estrogen therapy were associated with increased frequency of sexual activity, enjoyment, desire, arousal, fantasies, satisfaction, vaginal lubrication, and feeling physically attractive, and reduced dyspareunia, vaginal dryness, and sexual problems. Certain types of testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 41 publications
1
70
1
Order By: Relevance
“…3,4 Previous clinical studies have shown that women treated with testosterone were more likely to report benefits in different aspects related to sexual activity. 13,14 Regarding, other studies related with testosterone therapy in postmenopausal where taking estrogen failed, 20 our findings in this present study are contrary to previous ones 21,22 that have shown that the concurrent estrogen therapy interferes with exogenous testosterone. A recent study by Botelho et al 4 evaluated the comparative effects of transdermal estrogen therapy associated with progesterone.…”
Section: ■ Conclusioncontrasting
confidence: 57%
“…3,4 Previous clinical studies have shown that women treated with testosterone were more likely to report benefits in different aspects related to sexual activity. 13,14 Regarding, other studies related with testosterone therapy in postmenopausal where taking estrogen failed, 20 our findings in this present study are contrary to previous ones 21,22 that have shown that the concurrent estrogen therapy interferes with exogenous testosterone. A recent study by Botelho et al 4 evaluated the comparative effects of transdermal estrogen therapy associated with progesterone.…”
Section: ■ Conclusioncontrasting
confidence: 57%
“…Thus, this finding may reflect type I error. Despite previous randomized controlled trials showing estrogen therapy effects on sexual satisfaction, 59 hormone therapy did not have a significant impact on sexual satisfaction. Confounding by indication suggests that women with sexual dissatisfaction due to atrophic vaginitis may take exogenous estrogen.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, we operationally defined a substantial decline in sexual function as a 50% or greater reduction in the total DISF score relative to baseline scores. This criterion was intended to serve as a proxy for a clinically significant decrease in sexual function (Alexander et al, 2004) and was based on a similar threshold employed in pharmacologic studies of depression, in which a 50% improvement in rating scores is considered to be clinically significant. We compared the number of men and women who experienced a 50% or greater reduction (relative to baseline) in their total DISF scores by w 2 analysis.…”
Section: Discussionmentioning
confidence: 99%